The socio-economic effects of forest management on lives of people living in the area; the case of Central America and some Caribbean countries - Budowski, G (1981)
Four broad categories of forest management in Central America and some countries of the Caribbean, namely for protection, for wood production, for a combination of agriculture and forestry (agro-forestry) and for multiple use, are analyzed as to their present and potential impact on local populations living within or near the forest. Many problems resulting from past and present massive deforestations and lack of management are negatively affecting local populations. In the light of experience from the region, it appears that large reforestation schemes on land that has been degraded, would provide interesting opportunities for stable forest communities in the light of shortage of forest products and needs to control erosion. Capitalizing on present widespread agroforestry practices appears to be particularly promising in some areas but a better understanding of biological and social characteristics of some of the present systems, is required to launch successful improvement programmes. Some examples of multiple uses are also described notably the use of a national forest for recreation and the establishment of a biosphere reserve where the rights and customs of local populations are safeguarded.